Iron Deficiency and Hair Loss: Ferritin Cutoffs, Diagnostic Controversies, and Treatment Outcomes-An Updated Evidence Synthesis-Comprehensive Review - Luay Kareem , Hadeel; Enas D. Neama; Saad Al-Kawaz , Hawraa (Hammurabi Journal of Medical Sciences, 2026)
Clinical management for suspected iron associated non-scarring hair loss should be structured, context-sensitive, and not based solely on ferritin levels. The first step is proper phenotype determination (telogen effluvium/female pattern hair loss) based on history and physical examination of the scalp, including dermoscopy (if available). Laboratory evaluation is the most informative to look at ferritin but, it should be paired with hemoglobin indices, functional iron markers (ferritin, transferrin saturation) and with checking the inflammatory state (CRP). This combined approach results in the suppression of misclassification, particularly for patients in whom ferritin can be falsely normal or high because of inflammation. Treatment decisions should be individualized. Iron repletion is most defensible if it in telogen effluvium in which ferritin clearly is low and inflammation not distorting the biomarker. In ambiguous circumstances (non-anemia), then the choice should take into account shedding severity and duration, reproductive status and menstrual losses, dietary factors, and characteristic systemic symptoms in favor of deficiency. In female pattern hair loss, iron therapy should be reserved for the proven deficient, as the main causes of this type of hair loss are follicular miniaturization and genetic-androgenic, and there is no evidence to always pursue normality goals of ferritin. Follow-up should be on both biochemical responses, as well as in realistic timelines for improvement of hair. Ferritin and transferrin saturation may be rechecked after about 8-12 weeks in order to confirm trends of repletion when clinical improvement in shedding is usually delayed by the length of time taken for hair cycling to occur. Treatment usually needs to be ongoing beyond having the first laboratory improvement to increase the iron reserves, but prolonged therapy in the absence of actual deficiency should be avoided. Shedding scores used as consistent clinical tracking (and objective measures where this is possible) helps us to interpret response. Non-response to better iron markers gives reason for reassessment not escalation of iron. Common explanations are incorrect initial diagnosis (female pattern hair loss misdiagnosed as telogen effluvium), persistent inflammatory or endocrine disease occurrence, thyroid dysfunction or coexisting nutrition (D3, zinc, inadequate protein intake). In the case of female pattern hair loss, treatments (e.g., topical minoxidil, and other treatment specific to hair phenotype) grounded in evidence studies may be indicated irrespective of the iron status; one exception may be chronic telogen effluvium that may have multifactorial causes, and a broader workup may be indicated.